Pola plan mahasiswa jurusan sejarah Universitas Negeri Malang dalam KPL (Kajian dan Praktik Lapangan) II berbasis lesson study di Kota Malang - Alfia Hasanah; Mashuri Mashuri; Indah Wahyu Puji Utami (Universitas Negeri Malang, 2018)
This research purpose is to explore how history initial teachers plan their lesson for lesson study during the KPL (internship) on 8 schools in Malang. 22 subjects were observed and interviewed by researchers during the research. This research found that there are two patterns of planning conducted by the history initial teachers during their internship for their lesson study. First, the lesson plans were made collaboratively. Second, the lesson plans were made individually.DOI: 10.17977/um022v3i22018p069